New enlightenment on the regulatory effects of acids and phenolic compounds in wood vinegar, a by-product of biomass pyrolysis, on tomato production - Hongyin Zhou; Hongyin Zhou; Naiming Zhang; Liyuan Mu; Liu Gao; Li Bao; Caixian Tang (Frontiers in Microbiology, 2025)
Wood vinegar (WV), a biomass pyrolysis by-product, is widely used in agriculture because of the complexity and abundance of its bioactive substances. However, the specific mechanisms underlying plant growth regulation by acids and phenolic compounds, accounting for the largest proportion of their constituents, remain unclear. Therefore, the main acids (N-ethylglycine, Lactic, and 2-pyridinecarboxylic acids) and phenols (Catechol and Guaiacol) were selected to understand their effects on soil properties, microbial communities, and tomato growth in a pot experiment. Results showed that individual applications of acids and phenolics significantly enhanced nutrient availability (e.g., soil AP, AK, and AN), promoted tomato growth (e.g., PH, SD, AB), and regulated endogenous hormone levels (upregulating auxin (IAA), gibberellin (GA3 ), and cytokinin (CTK); downregulating abscisic acid (ABA). Among them, N-ethylglycine and catechol exhibited the most pronounced effects. However, their mixture (acid-phenolic combination) attenuated growth-promoting effects and hormonal regulation, accompanied by reduced bacterial community richness (ACE and Chao indices) and operational taxonomic units (OTUs) compared to single treatments. The dominant bacteria in the treatments with N-ethylglycine, Catechol, and their combination were Pedobacter, Pseudoxanthomonas, and TM7a, respectively, whereas the dominant fungi were Olpidiaster, Borealophlyctis, and Spizellomyces, respectively. Network-based analysis showed that Pseudoxanthomonas was negatively correlated with Pedobacter, and Olpidiaster was positively correlated with Spizellomyces. These findings deepened our understanding of the effects of acids and phenolics in WV on endogenous hormone levels, soil chemical characteristics, microbial diversity, and metabolic processes in tomato, and revealed the mechanisms of regulatory effects of WV components on crop growth.